Ultrafast Charge Transfer between Light Absorber and Co3O4 Water Oxidation Catalyst across Molecular Wires Embedded in Silica Membrane - Edri, Eran; Cooper, Jason K.; Sharp, Ian D.; Guldi, Dirk Michael; Frei, Heinz (Journal of the American Chemical Society, 2017)
The mechanism of visible light-induced hole transfer from a molecular light absorber, in the form of a free-base porphyrin, coupled to a Co3O4 nanoparticle catalyst for water oxidation by a molecular wire (p-oligo(phenylenevinylene) featuring three aryl units) is investigated by transient absorption spectroscopy. The wires are covalently anchored on the Co3O4 surface and embedded in a dense, yet ultrathin (2 nm), silica layer that separates light absorber and catalyst. The porphyrin is electrostatically adsorbed on the silica surface, and aqueous colloidal solutions of the core-shell particles are used for transient optical measurements. Pulsed optical excitation of the porphyrin results in rapid injection of the photogenerated hole onto the molecular wire and concurrent formation of reduced light absorber in less than 1 picosecond (ps). Ultrafast charge separation was monitored by transient absorption of the wire radical cation, which is given by bands in the 500 to 600 nm region and at 1130 nm, while formation of reduced porphyrin was characterized by absorption at 700 nm. Forward transfer of the hole to Co3O4 catalyst proceeds in 255 ± 23 ps. Ultrafast transfer of positive charge from the molecular assembly to a metal oxide nanoparticle catalyst for water oxidation is unprecedented. Holes on Co3O4 recombined with electrons of the reduced sensitizer with biphasic kinetics on a much longer time scale of ten to several hundred nanoseconds. The unusually efficient hole transfer coupling of a molecular light absorber with an Earth-abundant metal oxide catalyst by silica-embedded p-oligo(phenylenevinylene) offers an approach for integrated artificial photosystems featuring product separation on the nanoscale.
EAM Import::2019-03-13